The American Sign Language Handshape Game Cards : The American Manual Alphabet - Bahan, Benjamin J.
American Sign Language (ASL) is a visual-gestural language used by early three-quarters of a million North Americans. A language of this type operates differently from other languages that are audio-vocal. ASL uses certain parts of the body (gestural) to create "words" or signs that symbolize concepts and uses the eyes (visual) to "hear" what is being expressed. In short, a visual-gestural language is built according to the capabilitites of the body and eyes. All languages have building blocks that create words and sentences. ASL "words" are composed of building blocks called parameters. One sign is created from the combination of four parameters, which are handshape, palm orientation, movement and location. Where individual signs are created by the combination of parameters, sentences are created by combinations of signs along with non-manual signals (i.e. head movement, eye gaze, and eyebrow movement). There are different kinds of sentences in ASL. One of them probably ranks first in importance: it is the kind that includes Classifiers (more explanation is given about Classifiers on page 7). These Handshape cards are only an introduction to one of the four parameters, so bear in mind the importance of the other three. Some handshapes and their use in signs may vary according to regional and dialectic difference. Some regions may have a handshape that is not included in this set. A system of dot coding is provided to help you choose games that are appropriate for your skill level or the skill level of students